The Effect of Range of Motion (ROM) Nursing Action on Non-Hemoragic Stroke Patients with Physical Mobility Disorders - Hikma, Waode Erty; Mukin, Rovina Nini; Lestari, Dyah (Global Health Science Group, 2023)
Movement disorders can occur due to muscle weakness and inability to move due to damage to the nervous system in the brain and stiffness in the muscles and joints which can cause problems with the independence of post-stroke patients. As many as 80% of stroke patients experience weakness on one side of the body/hemiparesis (Gorman, 2014). This has an impact on Activity Daily Living (ADL) where a person will depend on others, either partially assisted or totally dependent. The purpose of this study was to describe the effect of ROM nursing on non-hemorrhagic stroke patients with impaired physical mobility. The research method used was a pre-experiment with One Group pre-test-post-test design, a sample of 78 respondents with consecutive sampling techniques who were given ROM exercises with 12 days of exercise with 2 times a day. The results showed that after being given ROM therapy for 2 weeks with two applications in the morning and evening within 10-15 minutes, data collection was obtained using an observation sheet. The statistical test used was the Wilcoxon test and a ρ value of 0.001 was obtained. The conclusion from the discussion of ROM exercises can stimulate increased neuromuscular activity, stimulate nerve fibers in the extremities, especially the parasympathetic nerves that create acetylcholine, thereby triggering contractions.